1987
DOI: 10.1029/rg025i001p00055
|View full text |Cite
|
Sign up to set email alerts
|

Slab pull and the seismotectonics of subducting lithosphere

Abstract: This synthesis links many seismic and tectonic processes at subduction zones, including great subduction earthquakes, to the sinking of subducted plate. Earthquake data and tectonic modeling for subduction zones indicate that the slab pull force is much larger than the ridge pusJa force. Interactions between the forces that drive and resist plate motions cause spatially and temporally localized stresses that lead to characteristic earthquake activity, providing details on how subduction occurs. Compression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 124 publications
5
90
0
Order By: Relevance
“…The force per unit length related to a general slab force is not easy to quantify also because it depends on various parameters such as the dip angle, the plate velocity, the penetration depth and probably more. In a first approximation pure slab pull forces have been estimated to be in the range of 5-15×10 12 N/m (Forsyth and Uyeda, 1975;Spence, 1987;Turcotte and Schubert, 2002). More recent simulations however, have suggested that the net slab pull force is of order 4-6×10 12 N/m (Bird et al, 2008;Schellart, 2004) which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
“…The force per unit length related to a general slab force is not easy to quantify also because it depends on various parameters such as the dip angle, the plate velocity, the penetration depth and probably more. In a first approximation pure slab pull forces have been estimated to be in the range of 5-15×10 12 N/m (Forsyth and Uyeda, 1975;Spence, 1987;Turcotte and Schubert, 2002). More recent simulations however, have suggested that the net slab pull force is of order 4-6×10 12 N/m (Bird et al, 2008;Schellart, 2004) which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
“…The origin of the Strait of Sicily rift is not fully understood, although the roughly north-south extension, about parallel to the coeval strike of the subducted Tyrrhenian slab, suggests the possible activity of a slab pull force (Spence 1987). As the Maghrebian fold-and-thrust belt encroached the continental lithosphere of the African margin, the arrival at the subduction zone of the buoyant continental lithosphere slowed down the subduction rate, maximizing the effect of slab pull on the subducted African lithosphere ( Fig.…”
Section: Geological and Geophysical Evidence For A Trench-parallel Tementioning
confidence: 99%
“…plates, as reviewed recently by Spence [1987], does, however, allow some characterization of these time average stresses. For example, the presumed dominance of slab pull as a driving force suggests that a" will correspond to extensional stresses in regions of the plate downdip from the thrust contact zone, that is, in the subducting slab zone of Figure 11.…”
Section: Consideration Of the Gravitational Loading Of Subductingmentioning
confidence: 99%